Autophagy-related 16-like 1gene polymorphism, risk factors for cardiovascular disease and associated carotid intima-media thickness in postmenopausal women - Orsatti, Claudio Lera [UNESP]; Sobreira, Marcone Lima [UNESP]; Sandrim, Valéria Cristina [UNESP]; Nahas-Neto, Jorge [UNESP]; Orsatti, Fabio Lera; Nahas, Eliana Aguiar Petri [UNESP] (Elsevier, 2018)
Background: Early identification of asymptomatic postmenopausal women (PW), who are more predisposed to developing cardiovascular disease (CVD), is an important preventive strategy. Autophagy-related 16-like 1 (ATG16L1) is an autophagy gene known to control host immune responses and is associated with a variety of diseases, including CVD. Objective: The aim of the study was to associate the ATG16L1 polymorphism variant with subclinical carotid atherosclerosis in asymptomatic PW. Study design: This cross-sectional study included 210 Brazilian postmenopausal women (age ≥ 45 years with amenorrhea ≥12 months). Clinical, anthropometric and biochemical assessments were performed to evaluate the cardiovascular risk factors. DNA was extracted from buccal cells and the ATG16L1 (T300A) polymorphism was determined by the polymerase chain reaction (PCR). The carotid intima-media thickness and/or the presence of plaques were evaluated by carotid duplex ultrasound. For statistical analysis, the t-test, logistic regression and analysis of covariance (ANCOVA) were used. Results: The presence of the polymorphic allele forATG16L1 (T300A) was found in 77.47% (A/G = 49.87%, G/G = 27.60%). The ATG16L1 (T300A) polymorphism is significantly associated with increased carotid intima-media thickness (IMT) after adjustments of the confounding variables (P <.037). No significant associations were observed between the polymorphism with other risk factors for CVD in PW. Conclusion: In postmenopausal women, the ATG16L1 (T300A) polymorphism is significantly associated with increased carotid IMT (marker of atherosclerotic disease) after adjustments of the confounding variables (P <.037). Thus, identifying the ATG16L1 polymorphism is an important strategy for screening asymptomatic PW who are more predisposed to developing CVD.
Keywords: ATG16L1; Atherosclerosis; Gene polymorphism; Inflammatory; Postmenopausal